THE ANALYSIS OF URINARY INCONTINENCE ON SEXUALITY (Fiep Bulletin - online, 2014)
Introduction: Urinary incontinence is a common condition, which has social implication, causing discomfort, embarrassment, loss of self-confidence, and may have negative effect on quality of life. In women, some situations, such as childbirth, estrogen deficiency, increased intra-abdominal pressure and chronic constipation, lead to the weakening and malfunctioning as a result of pelvic floor muscles causing various problems, such as loss of urine (urinary incontinence) and feces (fecal incontinence), genital prolapse (abnormal protuberances of internal organs) and sexual dysfunction. There are three types: stress urinary incontinence (SUI), urinary Urgency incontinence (overactive bladder – IUU FISHERIES), and the Mixed urinary incontinence. Given the negative effect on women's lifestyle, stands out in this study the urinary incontinence associated with low quality of life with negative impacts on sexual life. Objective: Analyze the influence of urinary incontinence on quality of sexual life of women. Methods: This is a study with quantitative characteristic of the descriptive type, directly aimed at data collection of forty women, including women who have urinary incontinence and sex life affected by the same, women who have urinary incontinence only without the sex life affected and women who did not present any of the diseases, through questionnaires in the period from July to August 2013 carried out only with female patients. Results: On the basis of the questionnaires applied was possible to identify that in a sample of 40 women, 57.5% of patients had problems with urinary incontinence and sex life affected by same, 25% of patients had problems with urinary incontinence without that this affects the sex life and 17.5%, i.e. 7 of the patients did not present urinary incontinence, and the consequent change in sex life. Conclusion: It is concluded from this study with females that no significant implications in an age group around, identifying that regardless of age if the patient presents with the painting of urinary incontinence, possibly there will be a reduction in the quality of sex life.
Keywords: Urinary Incontinence; Sex Life; Quality of life